2016
DOI: 10.3892/or.2016.5090
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of an expanding-type gastric cancer cell line by Ming's classification

Abstract: According to Ming's classification, gastric cancer (GC) can be divided into two types: expanding and infiltrative. The two types are readily recognizable by histology: expanding carcinomas grow en masse and by expansion, resulting in the formation of discrete tumour nodules, whereas in infiltrative carcinoma, tumour cells invade individually. Both types show varying degrees of cell maturation. The two types of carcinomas have vastly different pathological and clinical features. However, little is known concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The main challenge of exploring the impact of regulatory networks to histological classification is the establishment of cell line that origin from specific pathological type tissue of GC. To address this problem, the new GC cell lines of Ming’s classification XGC-1 and XGC-2 were established and characterized in our laboratory as previous report [ 26 ]. In this study, our results suggested that the dysregulaton of circRNA–miRNA network might be involved in differential patterns of growth and invasiveness of GC and provided new understanding of the biological role of circRNA–miRNA–mRNA regulatory network in GC development and clinical progression.…”
Section: Introductionmentioning
confidence: 99%
“…The main challenge of exploring the impact of regulatory networks to histological classification is the establishment of cell line that origin from specific pathological type tissue of GC. To address this problem, the new GC cell lines of Ming’s classification XGC-1 and XGC-2 were established and characterized in our laboratory as previous report [ 26 ]. In this study, our results suggested that the dysregulaton of circRNA–miRNA network might be involved in differential patterns of growth and invasiveness of GC and provided new understanding of the biological role of circRNA–miRNA–mRNA regulatory network in GC development and clinical progression.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many gastric cancer cell lines have been established from human tumours; these cell lines have served as important experimental tools in oncology research [6][7][8][9][10][11][12]. These cell lines have many advantages: they are very easy to handle, they are an infinite source of self-replicating cells, they have a relatively high degree of homogeneity, and they are easy to replace with frozen stocks if they become contaminated.…”
Section: Introductionmentioning
confidence: 99%
“…The rst human cancer cell line was established in a Baltimore laboratory by Gey et al [5] over 65 years ago. Since then, many gastric cancer cell lines have been established from human tumours; these cell lines have served as important experimental tools in oncology research [6][7][8][9][10][11][12]. These cell lines have many advantages: they are very easy to handle, they are an in nite source of self-replicating cells, they have a relatively high degree of homogeneity, and they are easy to replace with frozen stocks if they become contaminated.…”
Section: Introductionmentioning
confidence: 99%
“…However, these cell lines also have some shortcomings; cell lines easily undergo genotypic and phenotypic drift in culture, and this drift is particularly frequent in the more commonly used cell lines, especially those that have been deposited in cell banks for many years. In addition, through speci c mutations, some subpopulations that show rapid growth or increased malignancy may arise over time [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%